Salmonella choleraesuis and Salmonella typhimurium associated with liver cells after intravenous inoculation of rats are localized mainly in Kupffer cells and multiply intracellularly. - Nnalue, N A (1992)
Male Sprague-Dawley rats were inoculated intravenously with Salmonella choleraesuis or Salmonella typhimurium and used over 3 consecutive days to produce highly enriched (greater than 95% homogenous) preparations of Kupffer and mononuclear cells (KC), liver endothelial cells (LEC), and hepatocytes. The methods involved collagenase perfusion of the liver in situ, differential centrifugation of liver cells over a Percoll gradient, and selective attachment of the cells to plastic or to culture dishes coated with collagen. The different cell preparations were then assayed for the number and location, intracellular or extracellular, of associated viable bacteria. Most of the viable bacteria recovered were associated with KC and were mainly intracellular. The intracellular bacteria in KC from rats infected with either bacterial strain increased about 20- to 50-fold over 2 days. Some of the bacteria associated with LEC and in some experiments with hepatocytes also survived treatment with gentamicin and increased in number with time. Intracellular bacteria were readily visualized in KC by light microscopy and transmission electron microscopy. On rare occasions, bacteria were seen within LEC from rats infected with S. choleraesuis but not from those infected with S. typhimurium. Microcolonies of S. typhimurium but not of S. choleraesuis were occasionally found on the surface of some LEC. Bacteria were not seen within or on the surface of hepatocytes by transmission or scanning electron microscopy. The integration of microscopic and viability data suggested that most intracellular S. choleraesuis organisms in KC had been killed whereas most intracellular S. typhimurium organisms were viable.